2011
DOI: 10.3168/jds.2010-3536
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effects of replacing part of corn silage and alfalfa hay with Leymus chinensis hay on milk production and composition

Abstract: The objective of this research was to investigate the effects of replacing part of corn silage (CS) and alfalfa hay (AH) with Leymus chinensis hay on milk production and composition. Twenty multiparous Holstein dairy cows were used in a randomized block design for a 14-week period and 2 treatments. Treatments were (dry matter basis): (1) Non-Leymus chinensis hay diet (NLC; 35% CS, 15% AH) and (2) added Leymus chinensis hay diet (ALC; 30% CS, 10% AH, 10% Leymus chinensis hay). Adding Leymus chinensis hay increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…In addition, there was no difference in milk yield for cows fed diets containing AH, OH, LC, and RS as the main source of forage fiber. In some previous studies, the increased DMI was the primary reason for increased milk production (Yan et al, 2011), and the lack of difference in DMI may be due to the similar milk yield among the treatments (averaging 24.39 kg/d). Gencoglu et al (2007) observed that DMI, 4% FCM, and milk yield were similar in cows fed wheat straw compared to chopped alfalfa hay in the diets.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, there was no difference in milk yield for cows fed diets containing AH, OH, LC, and RS as the main source of forage fiber. In some previous studies, the increased DMI was the primary reason for increased milk production (Yan et al, 2011), and the lack of difference in DMI may be due to the similar milk yield among the treatments (averaging 24.39 kg/d). Gencoglu et al (2007) observed that DMI, 4% FCM, and milk yield were similar in cows fed wheat straw compared to chopped alfalfa hay in the diets.…”
Section: Discussionmentioning
confidence: 93%
“…; Yan et al . ). In China, alfalfa ( Medicago sativa L.) has been cultivated extensively in recent years.…”
Section: Introductionmentioning
confidence: 97%
“…Because of the economic importance of sheepgrass, the utilization and improvement of sheepgrass feedstocks have been broadly studied during the past decades (Chen et al, 2002, 2015; Wang et al, 2009). A good balanced diet for cows has been achieved by replacing part of corn silage and alfalfa hay with sheepgrass hay (Yan et al, 2011). However, the forage digestibility is highly variable in different sheepgrass germplasms (Xu and Zhou, 2006).…”
Section: Introductionmentioning
confidence: 99%